Analysis of Visual and Persuasive Language Used on Billboards Promoting Candidates of the 2019 Elections - Rahmawati, Lely; ., Emzir; Tajuddin, Shafruddin (KnE Social Sciences, 2020)
The 2019 elections were the first occurrence involving votes for the president, Regional Representative Board (DPD), House of Representative (DPR) and Regional House of Representative (DPRD) all on the same day. In this study, the billboards used in campaigns are investigated and their linguistic aspects scrutinised. The study uses a qualitative description analysis method, involving two billboards originating from the nationalist and Islamic camps which won the general elections in 2019. The study uses two approaches in analyzing the first billboard: 1) semiotic social analysis to analyze images and symbols on billboards and 2) persuasive discourse to analyze existing taglines. The study demonstrates the presence of a dominant type of persuasive discourse that contains an invitation and affirmation. On the billboard, the researchers found that the candidates used many key figures to increase their appeal and also used the billboards to educate voters about callot-casting, Keywords: general election, parties, languages, persuasive